2022
DOI: 10.3390/su14020794
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Carbon Neutral and Sustainable Campus: Case Study of NED University of Engineering and Technology

Abstract: Globally, universities are evaluating and targeting to reduce their carbon emissions and operate on a sustainable basis. The overall aim of this study revolves in addressing the following three questions: (1) How to calculate carbon footprint, including indicators selection, criteria, and measurement, for higher education institutions? (2) How to evaluate impact and effectiveness of various mitigation strategies in context of a higher education institution? (3) What are the possible limitations of approach sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Apart from households, universities can help reduce carbon emissions. Carbon emissions were quantified at the NED University of engineering and technology in Karachi, Pakistan, using a carbon calculator, and mitigating strategies were identified (Mustafa et al 2022 ). The data indicated that the campus produced 21,500 Mt CO 2 -eq in 2017, equating to 1.79 Mt CO 2 -eq per student.…”
Section: Achieving Carbon Neutralitymentioning
confidence: 99%
“…Apart from households, universities can help reduce carbon emissions. Carbon emissions were quantified at the NED University of engineering and technology in Karachi, Pakistan, using a carbon calculator, and mitigating strategies were identified (Mustafa et al 2022 ). The data indicated that the campus produced 21,500 Mt CO 2 -eq in 2017, equating to 1.79 Mt CO 2 -eq per student.…”
Section: Achieving Carbon Neutralitymentioning
confidence: 99%
“…This entails that universities act as anchors in the local and global communities they serve as they lead in technological and scientific innovations in educating professionals and conducting research (Mustafa et al , 2022). Hence, they are ideal testing grounds where sustainability solutions can be experimented and demonstrated, in the form of living laboratories (LL) (Mustafa et al , 2022). Definitions of LL vary amongst researchers depending on the environment that the concept is rooted in and the desired outcome.…”
Section: The Role Of Universities In Sustainability Transitions and I...mentioning
confidence: 99%
“…The carbon footprint of NED University's main campus was computed by using Clean Air Cool Planet (CA-CP) Carbon Calculator, originally developed by the non-profit organization Clean Air-Cool Planet and the Sustainability Institute at the University of New Hampshire (USA), and reported as 21,500 ๐‘ก๐‘ก๐ถ๐ถ๐ถ๐ถ 2 ๐‘’๐‘’๐‘’๐‘’ for the year 2017 28) . However, to enhances the credibility and simplicity of calculating the CF, the ๐ถ๐ถ๐ถ๐ถ 2 emissions caused by products must be assessed throughout their life cycle; for this a product carbon footprint can be determined by using a Life Cycle Assessment (LCA) method 8) .…”
Section: Introductionmentioning
confidence: 99%